Is qSOFA Suitable for Early Diagnosis of Sepsis Among Bacteremia Patients in Emergency Departments? Time for a Reappraisal of Sepsis-3 Criteria - Lee, Ching-Chi; Ho, Ching-Yu; Chen, Po-Lin; Hsieh, Chih-Chia; Wang, William Yu Chung; Lin, Chih-Hao; Ko, Wen-Chien (Frontiers in Medicine, 2021)
Background: To early recognize patients with sepsis, quick Sequential Organ Failure Assessment (qSOFA) was proposed by Sepsis-3 criteria as initial sepsis identification outside of intensive care units; however, the new definition subsequently has led to controversy and prompted much discussion for delayed treatment efforts. We aimed to validate Sepsis-3 criteria on bacteremia patients, by investigating prognostic impacts of inappropriate administration of empirical antimicrobial therapy (EAT) and delayed source control (SC), compared to Sepsis-2 criteria. Methods: In the multicenter cohort of adults with community-onset bacteremia in emergency departments (EDs), adverse effects of delayed treatment efforts on 30-day mortality were respectively examined in septic and non-septic patients with fulfilling the Sepsis-2 or Sepsis-3 criteria, using the Cox-regression model after adjusting independent determinants of mortality. Results: Of the total 3,898 adults, septic patients accounted for 92.8% (3,619 patients) by Sepsis-2 criteria (i.e., SIRS criteria). Using Sepsis-3 criteria, 1,827 (46.9%) patients were early diagnosed with sepsis (i.e., initial qSOFA scores ≥ 2) in EDs and 2,622 (67.3%) with sepsis during hospitalization (i.e., increased SOFA scores of ≥ 2 from ED arrival). The prognostic impacts of inappropriate EAT or delayed SC (for complicated bacteremia) were both significant in septic patients with fulfilling the Sepsis-2 or Sepsis-3 (i.e., SOFA) criteria, respectively. Meanwhile, these delayed treatment efforts trivially impact prognoses of non-septic patients recognized by the Sepsis-2 or Sepsis-3 (i.e., SOFA) definitions. Notably, prognostic effects of inappropriate EAT or delayed SC were disclosed for septic patients in EDs, namely qSOFA scores of ≥ 2, and prognostic impacts of delayed treatment efforts remained significant for patients initially early recognized as being non-septic (i.e., initial qSOFA scores of < 2). Conclusions: For patients with community-onset bacteremia, inappropriate EAT and delayed SC might result in unfavorable outcomes of patients early identified as being non-septic at ED arrival, based on the qSOFA scores (by Sepsis-3 criteria). Accordingly, a more prudent diagnosis of sepsis adopted among bacteremia patients in the ED is necessary.